Concurrent bilateral juvenile temporal arteritis and hypereosinophilic syndrome: a case report and review of the literature - Shim, Ji-Su (Asia Pac Allergy, 2019)
Most of temporal arteritis occurs in the older patient over 50 years old, and the histopathologic finding shows a granulomatous inflammation, so this called giant cell arteritis. However, the young patients also present with a nodular lesion in their temple, and juvenile temporal arteritis (JTA) should be considered as one of the differential diagnosis, although it is very rare. For both diagnosis and treatment of JTA, excisional biopsy is essential. The pathologic finding of the temporal artery shows panarteritis with lymphoeosinophilic infiltrates, but no giant cell or granulomatous lesion. JTA is a localized disease with low level of systemic inflammatory marker, so the symptom is usually relieved by excision of affected lesion. Peripheral blood eosinophilia present in some cases of JTA, but its relation with clinical course and prognosis is not yet been known. Herein, we report the case of a 24-year-old man diagnosed with concurrent JTA and hypereosinophilic syndrome. We also reviewed the literature of JTA focusing on the impact of combined peripheral eosinophilia on the course of the disease. Combined peripheral eosinophilia may increase the risk of recurrence of JTA after local treatment such as excision only.